Society and the death of God - Restivo, Sal P., author.
1 online resource.
Keywords: "This book advances the 'strong' programme that sociology and anthropology provide a scientific foundation for arguing that God and the gods are human creations. Contending that religion is one - but not the only - way to systematize and institutionalize the moral order of a society, the author argues that religion reflects the fundamental human need for belonging and the social function of compassion. As such, our transcendental and supernatural ideas are really concerned with our everyday lives in communities and, faced with severity and immediacy of the global problems with which the world is confronted - existential threats - it is increasingly important to abandon delusions and correct our mistake in reference, not by eradicating religion, but by grounding it more explicitly in earthly matters of community, social solidarity, belonging and compassion. A wide-ranging study of the roots, nature and purpose of religion and theistic belief, Society and the Death of God will appeal to sociologists, social theorists and philosophers with interests in the scientific study of religion and the role of religion in the life of humankind"--